INTERROGATING LEGAL IMPLICATIONS OF CONTEMPORARY ARTIFICIAL INTELLIGENCE EXPLORATIVE REGIME - Badr, Mohammed Bashir (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
The intersection of law and artificial intelligence (AI) is rapidly evolving, presenting both opportunities and challenges. The paper adopts doctrinal method to explore the legal implications of AI technologies, focusing on issues such as accountability, liability, privacy, and ethical considerations. As AI systems become more autonomous, questions arise regarding the allocation of responsibility for decisions made by these systems. It also examines the lawyers’ professional responsibility to client with the emergence of AI. The paper examines existing legal frameworks and their adequacy in addressing the unique characteristics of AI, proposing potential regulatory approaches to ensure that AI development and deployment align with societal values and legal standards. Additionally, the ethical dimensions of AI, including bias, transparency, and fairness, are discussed, highlighting the need for interdisciplinary collaboration to create robust and adaptive legal structures. By analyzing current case studies and legal precedents, this paper aims to provide a comprehensive overview of the challenges and potential solutions in the realm of law and AI.